2020
DOI: 10.5551/jat.49106
|View full text |Cite
|
Sign up to set email alerts
|

AEBP1 Promotes the Occurrence and Development of Abdominal Aortic Aneurysm by Modulating Inflammation via the NF-κB Pathway

Abstract: Inflammation plays a significant role in the pathogenesis of human abdominal aortic aneurysm (AAA). AEBP1 can promote activation of the NF-B pathway, subsequently affecting the expression of NF-B target genes, including inflammatory cytokines and matrix metalloproteinases (MMPs). Our objective was to examine the role of AEBP1 in the development of AAA and characterize the underlying mechanism.Methods: ITRAQ, RT-PCR, western blot, immunohistochemistry, and ELISA were used to compare different experimental group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 47 publications
(52 reference statements)
1
18
0
Order By: Relevance
“…Intraluminal perfusion with elastase model, one of the most widely used experimental models of AAA in vivo, was first introduced by Anidjar et al in Wistar rats [ 27 ], which simulates the pathological characteristics of medial degeneration and leukocyte infiltration in the occurrence and development of human AAA [ 28 , 29 ]. In this study, we established the elastase-induced AAA model in SD rats, and the abdominal aortas were morphologically aneurysmal on the 14th postoperative day, which is consist with previous investigations [ 24 , 30 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Intraluminal perfusion with elastase model, one of the most widely used experimental models of AAA in vivo, was first introduced by Anidjar et al in Wistar rats [ 27 ], which simulates the pathological characteristics of medial degeneration and leukocyte infiltration in the occurrence and development of human AAA [ 28 , 29 ]. In this study, we established the elastase-induced AAA model in SD rats, and the abdominal aortas were morphologically aneurysmal on the 14th postoperative day, which is consist with previous investigations [ 24 , 30 ].…”
Section: Discussionsupporting
confidence: 75%
“…In this study, elastase infusion method was implemented to establish an in vivo model of AAA in male SD rats following previous established protocols [24]. Briefly, after animals were anesthetized with gas mixture of 2% isoflurane and 2 L/min oxygen, midline abdominal incision was performed, the segment between left renal vein and bifurcation of abdominal aorta was carefully isolated and exposed, and then the infrarenal abdominal aorta was perfused with elastase (30 U/mL; Solarbio Life Sciences) or saline through PE-10 catheter under 130 cm water column pressure for 30 min.…”
Section: Establishment Of Aaa Model and Experimental Designmentioning
confidence: 99%
“…Interestingly, the nuclear localization of NF-κB/p65 was observed in specific neurons with AEBP1 overexpression [24]. AEBP1 has also been shown to play a role in abdominal aortic aneurysm (AAA) [25]. AEBP1 overexpression in AAA results in the activation of NF-κB/p65 and the consequent upregulation of inflammatory cytokines IL-1β, IL-6, TNFα, and MCP-1, as well as MMP2 and MMP-9, matrix metalloproteinases (MMPs) [25].…”
Section: Introductionmentioning
confidence: 99%
“…AEBP1 has also been shown to play a role in abdominal aortic aneurysm (AAA) [25]. AEBP1 overexpression in AAA results in the activation of NF-κB/p65 and the consequent upregulation of inflammatory cytokines IL-1β, IL-6, TNFα, and MCP-1, as well as MMP2 and MMP-9, matrix metalloproteinases (MMPs) [25]. In addition, modulation of AEBP1 expression has been implicated in other processes and conditions such as adipogenesis [2,5,6,11,26,27], mammary gland development [28][29][30], macrophage cholesterol homeostasis [8,12,31], inflammation [8,25,28,32], and atherosclerosis [32].…”
Section: Introductionmentioning
confidence: 99%
“…The AEBP1 protein could positively regulate the activity of MAP kinase (MAPK) in adipocytes, thus stimulating adipocyte proliferation and reducing adipocyte differentiation; the proteins can also positively regulate NF- κ B activity in macrophages by promoting I-kappa-B-alpha (NFKBIA) phosphorylation and subsequent degradation, thereby enhancing the inflammatory responsiveness of macrophages [ 5 ]. AEBP1 is involved in the progression of a variety of diseases, such as abdominal aortic aneurysm [ 6 ], nonalcoholic steatohepatitis [ 7 ], Ehlers-Danlos syndrome [ 8 ], and Alzheimer's disease [ 9 ]. Studies have shown that AEBP1 is highly expressed in a variety of malignant tumors (such as breast cancer, glioblastoma, bladder cancer, gastric cancer, colorectal cancer, ovarian cancer, and skin cancer) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%